Two Basal Cell Carcinomas of the Axillae: A Metastasis or an Independent Development? - Yuichiro Endo; Yoshiki Miyachi (Hindawi Limited, 2015)
Cutaneous basal cell carcinoma (BCC) is a common malignancy amongst the elderly. BCC rarely metastasises, and fewer than 300 cases of metastatic BCC have been reported in the literature. Here, we report a case of sequentially developed BCCs located adjacent to each other. We discuss that these BCCs were considered to have developed independently rather than due to metastasis, after referencing previous studies on metastatic BCC.